INFLUENCE OF FINAL TEMPERATURE AND Na2CO3 ADDITIVE ON REDUCTION PROCESS OF ILMENITE CONCENTRATE BRIQUETTE USING COAL-BED REDUCTOR WITH ISOTHERMAL- GRADIENT TEMPERATURE METHOD - YULIANTON, TOTO
Ilmenite is found worldwide in primary massive deposits or as secondary alluvial deposits containing heavy minerals. Increasing demand for raw materials with high TiO2 contents has led to development of synthetic TiO2 raw materials. In all production processes, iron is removed from ilmenite. The Sasabe method is intended to selectively remove the titanium element in the reduction of iron sand concentrate at a temperature range of 1350-1500 oC by gradient temperature method. The method can be applied to separate the ferrous metals from the ilmenite concentrate. The reduction of Ilmenite briquettes using coal bed reducers with variations in the addition of soda ash (Na2CO3) and the final temperature by temperature isothermal-gradient method has not been done. Therefore, in this study the Sasabe method is applied and combined with isothermal methods. . A series of experiments was conducted with variations in the addition of soda ash and final temperature. Initial characterization of the concentrate was done by XRay Diffraction (XRD) and X-Ray Fluorescence (XRF), while coal characterization was done by proximate test and ash component test. The sample used in this experiment is composite briquette which is a mixture of preoxidized, coal, and soda ash concentrate. Added soda ash variation is 10%; 20%, and 30%. Furthermore, the composite briquette reduction process is carried out by isothermal-gradient method of temperature which starts with isothermal heating at 1000 °C for 20 minutes. Then the temperature is increased to 1300-1500 °C with heating rate of 10 °C/min. In the last stage, reheating is carried out isothermally for 60 minutes. The result of reduction in the form of briquettes with iron nugget on the inside. The nuggets are then weighed in weight and measured in diameter. In addition, the reduction results are also analyzed by Scanning Electron Microscope (SEM) equipped with Energy Dispersive Spectrometer (EDS) and XRD. The reduction product of the isothermal-gradient method indicates a reduction in weight, there is a cavity in the middle of the product at a temperature of 1400 oC and 1500 oC with the addition of 20% and 30% soda ash. X-ray mapping results show that metallic iron is dominant in nuggets that are formed. Addition of soda ash and variations in final temperature affect ferrous metal recovery. Reduction at 1300-1500 oC with 10% soda ash does not produce iron nuggets. The highest average nugget diameter was obtained at reduction temperature of 1500 oC and the addition of 30% soda ash. Highest iron recovery was obtained in addition of 30% soda ash and temperature 1500 oC that was equal to 33,16%.